Biophysical Stimuli as the Fourth Pillar of Bone Tissue Engineering - Hao, Zhuowen; Xu, Zhenhua; Wang, Xuan; Wang, Yi; Li, Hanke; Chen, Tianhong; Hu, Yingkun; Chen, Renxin; Huang, Kegang; Chen, Chao; Li, Jingfeng (Frontiers in Cell and Developmental Biology, 2021)
The repair of critical bone defects remains challenging worldwide. Three canonical pillars (biomaterial scaffolds, bioactive molecules, and stem cells) of bone tissue engineering have been widely used for bone regeneration in separate or combined strategies, but the delivery of bioactive molecules has several obvious drawbacks. Biophysical stimuli have great potential to become the fourth pillar of bone tissue engineering, which can be categorized into three groups depending on their physical properties: internal structural stimuli, external mechanical stimuli, and electromagnetic stimuli. In this review, distinctive biophysical stimuli coupled with their osteoinductive windows or parameters are initially presented to induce the osteogenesis of mesenchymal stem cells (MSCs). Then, osteoinductive mechanisms of biophysical transduction (a combination of mechanotransduction and electrocoupling) are reviewed to direct the osteogenic differentiation of MSCs. These mechanisms include biophysical sensing, transmission, and regulation. Furthermore, distinctive application strategies of biophysical stimuli are presented for bone tissue engineering, including predesigned biomaterials, tissue-engineered bone grafts, and postoperative biophysical stimuli loading strategies. Finally, ongoing challenges and future perspectives are discussed.